When a woman ascends the stairs [videorecording (DVD)] = Onna ga kaidan o agaru toki - Naruse, Mikio, 1905-1969; Kikushima, Ryūzō, 1914-1989; Takamine, Hideko, 1924-2010 (Criterion collection, 2007)
A young widow with family obligations, Keiko is the madam of an upstairs bar in the exclusive Ginza district of Tokyo in 1960. As she approaches 30, she realizes that her life is at a crossroads: she must either go into business and open her own bar or marry.